2000
DOI: 10.1091/mbc.11.11.3675
|View full text |Cite
|
Sign up to set email alerts
|

ACAT1 and ACAT2 Membrane Topology Segregates a Serine Residue Essential for Activity to Opposite Sides of the Endoplasmic Reticulum Membrane

Abstract: A second form of the enzyme acyl-CoA:cholesterol acyltransferase, ACAT2, has been identified. To explore the hypothesis that the two ACAT enzymes have separate functions, the membrane topologies of ACAT1 and ACAT2 were examined. A glycosylation reporter and FLAG epitope tag sequence was appended to a series of ACAT cDNAs truncated after each predicted transmembrane domain. Fusion constructs were assembled into microsomal membranes, in vitro, and topologies were determined based on glycosylation site use and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
124
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(129 citation statements)
references
References 36 publications
3
124
1
Order By: Relevance
“…ACAT2 has only two transmembrane domains, with both the N and C termini facing the cytosol (29). A second study reported that both ACAT1 and ACAT2 have five transmembrane domains, with their N and C termini on opposite sides of the ER membrane (28). It has been speculated that the different membrane topologies observed for ACAT1 and ACAT2 may be due to significant differences in the amino acid sequences within the putative transmembrane domains (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ACAT2 has only two transmembrane domains, with both the N and C termini facing the cytosol (29). A second study reported that both ACAT1 and ACAT2 have five transmembrane domains, with their N and C termini on opposite sides of the ER membrane (28). It has been speculated that the different membrane topologies observed for ACAT1 and ACAT2 may be due to significant differences in the amino acid sequences within the putative transmembrane domains (29).…”
Section: Discussionmentioning
confidence: 99%
“…The membrane topologies of human ACAT1 and ACAT2, which share 15-25% identity with DGAT1, have been determined. ACAT1 appears to have 5-9 transmembrane domains with the N terminus facing the cytosol and the C terminus in the ER lumen (27,28). Two different models have been proposed for human ACAT2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the enzymological properties of ACAT isozymes are also very similar [41], the exact membrane topology and the active site of ACAT isozymes remain unresolved. Joyce et al reported that the active site of ACAT1 (Ser 269 ) is located in the cytoplasm, while that of ACAT2 (Ser 249 ) is located in the lumen [42]. On the other hand, Chang et al reported that the active site of ACAT1 (His 460 ) and ACAT2 (His 434 ) is located in the transmembrane domain [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Like DGATs, two genes that encode ACAT1 and ACAT2 have been identified with distinct roles (35)(36)(37). Although the membrane topology of ACAT2 is still controversial (38,39), it secretes more VLDL cholesterol compared with ACAT1 when overexpressed in RH7777 cells (27). These data suggest that DGAT1 and ACAT2 might coordinately participate in VLDL formation within the ER lumen.…”
Section: Discussionmentioning
confidence: 99%